The Influence of Quality of Work Life on Work Engagement: The Mediating Role of Burnout, Supervisor Support, and Career Identity - Budiarti Mastuti Indrianingsih, Tiwik; Laksmi Riani, Asri (International Journal of Science, Technology & Management, 2024)
This study aims to explore the relationship between burnout, supervisor support, career identity, quality of work life, and work engagement among nurses at Indriati Solo Baru Hospital, Sukoharjo, Central Java, Indonesia. A quantitative research method was employed, including descriptive analysis and Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis, using the SmartPLS application. The findings indicate that burnout and supervisor support are significantly correlated with the level of work engagement, while career identity exerts a strong influence on work engagement. Moreover, quality of work life is proven to play a crucial role as a mediator in the relationship between these variables. The practical implications of this study emphasize the importance of prioritizing the quality of work life, providing leadership training for supervisors, and developing employees' career identities to enhance work engagement